Life in the old stone age - Higham, Charles (Cambridge [Eng.] ; New York : Cambridge University Press, 1979)
An account of the discoveries of the remains of early man and a reconstruction of his life as it must have been.
Keywords: Paleolithic period -- Juvenile literature; Human evolution -- Juvenile literature